Development of a systematic technique for simultaneous reduction of energy and water in chemical process plants - Lim, Fang Yee; Abdul Manan, Zainuddin (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
Water and energy are the two main operating costs in a chemical process plant. With the increase in water and fuel prices, chemical process industries are under pressure to improve their profit margin or face possible closure of plants. Pinch and exergy analyses are techniques that have been used widely for plant energy and water consumption analysis. Pinch Analysis is an energy optimisation tool that can present system information by the use simple diagrams like the Composite Curves and Grand Composite Curves, and thus, provide energy consumption targets prior to design. Exergy analysis, also known as availability analysis is a powerful thermodynamics analysis tool that can provide a quick assessment of the energy efficiency of selected equipment and processes. Both approaches have been widely used as separate tools for improving chemical processes, but have key disadvantages that can hamper practical implementation of the project. In this paper, a novel, simple and systematic approach for simultaneous reduction of water and energy in the chemical process industries is presented. This new approach for the retrofit of existing process heat recovery system is focused, and requires significantly less diagnosis effort The procedure is also easy to use and designer is in control during process retrofit. The equipment causing the highest energy and water losses will be identified in order to reduce the utility consumption. Economic analysis will be conducted to assess the benefits of the improvement.